Application of qualitative content analysis for identifying performance evaluation domains of nurse faculties - Pazargadi, M; Khatiban, M; Ashketorab, T (Advances in Nursing & Midwifery, 2008)
Background Nurse faculty members are the backbone of nursing schools to move toward their mission and goals. Therefore, their performance should be identified and evaluated to identify the attainment of organizational goals. Purpose The purpose of this qualitative study was to identify main performance evaluation domains of nurse faculty members. Methods Data were collected by individual semi-structured interviews with authorities and inspection of actual evaluation forms, procedures and policies. The qualitative content analysis was applied in 22 transcriptions of the individual interviews and 26 sets of actual evaluation documents. The purposive sampling method was used for the selection of experts and all actual evaluation forms, procedures and policies were collected. Results Three main domains including personal competencies of lecturer, process of task accomplishment as well as task outcome and their components were abstracted by the analysis. Conclusion Evaluation of the three domains emphasizes on mix combination of three primary systems for performance evaluation of nurse faculty members, namely, personal competencies, process-based and mission-based. Keywords: Performance evaluation domains, Nurse faculty members, Qualitative content analysis.